Development of Augmented Reality Media Based On Cybernetic Learning Theory to Stimulate Spatial Abilities - Andriyani Andriyani; Joko Lianto Buliali; Yudhiakto Pramudya (Department of Special Education, 2022)
Hearing impairment students have limited vocabulary and have difficulty understanding abstract terms, which affects learning the concept of a plane solid figure that they know at school. Deaf students tend to have difficulty perceiving objects from a certain point of view and understanding the relationship between these objects in a particular space. These difficulties affect students' spatial abilities and require special handling in the form of learning-oriented to the learning process, not learning outcomes. The learning process itself can be determined by information systems such as the basis of cybernetic theory and supported by information technology-based interactive learning media. Therefore, this study aims to develop augmented reality media based on cybernetic learning theory to stimulate valid and practical spatial abilities of deaf students. The research and development model carried out in this study is the Borg and Gall model, which has systematic and descriptive steps for practical problems in teaching through applied research. Researchers collected data through validation questionnaires and student response questionnaires. Data analysis was carried out qualitatively and quantitatively. The augmented reality media developed here can be said to meet the criteria of validity and practicality based on the results of the product feasibility test. This media has also proven to be a solution in helping teachers to stimulate the spatial abilities of deaf students through a meaningful learning process determined by a technology-assisted information system